Embodied Methods in Critical Health Communication - Ellingson, Laura L. (Frontiers in Communication, 2019)
At the center of questions posed about power are issues of embodiment—which bodies are judged to be healthy and which are not, which identities are affirmed or privileged and which are stigmatizes or marginalized, which material practices are pathologized and which are lauded. Critical health communication research may be enacted by critical-interpretive researchers who employ critical theorizing frameworks that guide their questions posed, co-construction of data, and forms of analysis and representation.